Effect of Error Culture and Learning Organization Principles on Performance Enhancement Strategies within Organizations - Ghaleb, Belal Dahiam Saif (International Journal of Multidisciplinary Approach Research and Science, 2025)
This comprehensive literature review examines the intricate relationship between error culture, learning organization principles, and performance enhancement strategies within contemporary organizations. Through systematic analysis of empirical studies, theoretical frameworks, and meta-analytical research, this article synthesizes existing knowledge to establish how organizational approaches to error management and learning culture significantly influence performance outcomes. The findings demonstrate that organizations fostering constructive error management cultures—characterized by psychological safety, open communication, and systematic learning from mistakes—consistently outperform those maintaining error-averse environments. Similarly, organizations implementing learning organization principles, including systematic problem-solving, experimentation, knowledge transfer, and continuous improvement, exhibit superior performance across multiple dimensions. The analysis reveals that these two constructs interact synergistically, creating a powerful foundation for sustainable performance enhancement. This article contributes to organizational theory by providing an integrated framework that connects error culture, learning organization principles, and performance enhancement strategies, offering practical implications for organizational development and future research directions.